Enhancement of Flow Properties Biodiesel Using Sorbitan Monooleate - Herlin Arina; Mohammad Nasikin (Testing Center for Oil and Gas LEMIGAS, 2022)
Depletion of fossil fuel and increased pollution caused by the burning of fossil fuel is a leading factor in to use of alternate energy especially palm oil biodiesel as a mixture of diesel oil fuel (B-XX). It was reported that the use of the B-20 caused a blockage in the vehicle’s fuel filter. The blockage is caused by the presence of deposits formed from the agglomeration of monoglycerides. Three different biodiesels with monoglyceride content were used 0.40% - 0.60% by mass. The addition of monoglyceride standards (monopalmitin, monostearin, and monoolein) to biodiesel increases the volume of monoglyceride precipitates formed. The presence of these deposits decreases the flow properties of B-20. Research has been carried out to improve the flow properties of biodiesel by adding Sorbitan Monooleate (CMOST) surfactant, especially cloud points (CP) and cold filter plugging point (CFPP) parameters. The addition of 0.10%w - 1%w CMOST can reduce the CP by 4.80oC and CFPP by 2oC. This proves that the addition of SMO will improve the flow properties of B-XX as an alternative energy.